Faktor Pengaruh Perkawinan Usia Muda Dampaknya Terhadap Pola Asuh Orangtua Di Desa Setialaksana - Andri Cahyo Purnomo (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2017)
This study aims to describe the factors that affect the marriage of young age and to describe the parenting patterns of young couples couples. The results of this study are expected to be an input for parents, so as not to rush to immediately marry children at a young age. Because of the young age here which can also be called adolescents have not been able to deal with and solve the problems of the household well. The teenagers still need to stock a lot of good stock of physical maturity, mental and social economy, general science, religion, life experiences in married life. The research was conducted in Setialaksana Village Branch District of Bekasi Cabangbungin. This research is descriptive research, where informant in this research is adolescent who have married at young age that is as much 20 people and parents from informant 23 people. Data collection techniques with literature study, field study, in-depth interviews, triangulation with expert opinion, and observation. The data obtained in the field then analyzed and arranged in the draft of question and answer between the researchers described qualitatively. Triangulation results with the head of the Office of Religious Affairs (KUA) Cabangbungin District, it was found that why married young can not live happily when the household is a measure of happiness is not merely wealth is abundant but the happiness of love and commitment to be the ultimate happiness. But it's good readiness of each individual to marry both physically and mentally should not be ignored because marriage is an important and sacred thing that is searched by the spouse semidup semati. The result of this research show conclusion that environmental factor of society and parent enough influence toward the formation of self concept in children, because the child see that many mother also do young marriage. Factors low economic level of parents cause many parents marry their children at a young age.